Utilization of Clustered Regularly Interspaced Short Palindromic Repeats to Genotype Escherichia coli Serogroup O80 - Long, Jinzhao; Xu, Yake; Ou, Liuyang; Yang, Haiyan; Xi, Yuanlin; Chen, Shuaiyin; Duan, Guangcai (Frontiers in Microbiology, 2020)
The hypervariable nature of CRISPRs (clustered regularly interspaced short palindromic repeats) makes them valuable biomarkers for subtyping and epidemiological investigation of Escherichia coli. Shiga toxin-producing E. coli (STEC) serogroup O80 is one hybrid pathotype that is emerging recently in Europe and is involved in hemolytic uremic syndrome (HUS) with bacteremia. However, whether STEC O80 strains can be genotyped using CRISPR has not been evaluated. In this study, we aimed to characterize the genetic diversity of 81 E. coli serogroup O80 isolates deposited in the NCBI databases using CRISPR typing and to explore the association between virulence potential and CRISPR types (CTs). A total of 21 CTs were identified in 80 O80 strains. CRISRP typing provided discrimination with variants of a single ST or serotype, which suggested a stronger discriminatory power. Based on CRISPR spacer profiles, 70 O80:H2 isolates were further divided into four lineages (lineage LI, LII, LIII and LIV), which correlated well with wgSNP typing and virulence gene profiles. Moreover, the association between CRISPR lineages and virulence gene profiles hinted that STEC O80:H2 strains may originate from O80:H19 or O80:H26 and that lineage LI may have been evolved from lineage LII. CT2 and CT13 were shared by human and cattle isolates, suggesting that there might be the potential transmission between cattle and human. Collectively, CRISPR typing is one technology that can be used to monitor the transmission of STEC O80 strains and provide new insights into microevolution of serogroup O80.